Investigation of proprioceptive sense in team and individual athletes - Emine Busra Aydin (ROL Spor Bilimleri Dergisi)
Proprioception is important for both athletic success and the post-injury process. This study aims to examine the proprioceptive senses of team athletes and individual athletes in different branches. A total of 250 volunteer athletes from Ondokuz Mayıs University Faculty of Sports Sciences participated in the study. The athletes were selected from soccer, basketball, volleyball, handball, taekwondo, tennis, athletics and other individual branches (boxing, kickboxing, karate, wushu, muaythai).  The mean age of the students was 20.44±1.73. In the study, dominant shoulder, non-dominant shoulder, dominant knee, and non-dominant knee proprioception measurements of the athletes were made. Since the data did not show a normal distribution, Kruskal Wallis test was used in comparisons between groups. Dunn’s multiple comparison test was used for subgroup comparisons. Mann Whitney U test was preferred for paired group comparisons. According to results proprioceptive sense is not differ according to gender (p>0.05). Dominant and non-dominant knee proprioceptive senses of team athletes were better than individual athletes (p<0.05). Participants who did regular weight training had better non-dominant knee proprioception than those who did not (p<0.05). Proprioceptive senses of both knees of soccer players were more developed than volleyball players (p<0.05). Soccer players had better non-dominant knee proprioception than handball players, and basketball players had better non-dominant knee proprioception than volleyball players (p<0.05). Proprioceptive sense of both knees or shoulder joints did not differ according to individual branches (p>0.05). Proprioceptive sense varies in athletes according to their branches.